1 / 8

80 likes | 177 Vues

REVIEW 7-2. Exponential Functions. 3 ----- 3x - 4 . Find the derivative:. 1. f(x) = ln(3x - 4). 2. f(x) = ln[(1 + x)(1 + x2) 2 (1 + x3) 3 ]. ln(1 + x) + ln(1 + x 2 ) 2 + ln(1 + x 3 ) 3. ln(1 + x) + 2 ln(1 + x 2 ) + 3 ln(1 + x 3 ).

Télécharger la présentation
## REVIEW 7-2

**An Image/Link below is provided (as is) to download presentation**
Download Policy: Content on the Website is provided to you AS IS for your information and personal use and may not be sold / licensed / shared on other websites without getting consent from its author.
Content is provided to you AS IS for your information and personal use only.
Download presentation by click this link.
While downloading, if for some reason you are not able to download a presentation, the publisher may have deleted the file from their server.
During download, if you can't get a presentation, the file might be deleted by the publisher.

E N D

**REVIEW 7-2**Exponential Functions**3. y = ln(cosx + 8x)**-sinx + 8cosx + 8x 4. y = ln(ln12x) 1__x__ln12x 1__xln12x = 5. y = 9xln2x 9x(1/x) + 9ln2x 9 + 9ln2x**6. y = ex2**7. y = sin(e3x).**SOLVE:**8. ln (x + 4) + ln (x - 2) = ln 7 ln (x + 4)(x - 2) = ln 7 eln (x + 4)(x - 2) = eln 7 (x + 4)(x - 2) = 7 x2 + 2x - 8 = 7 x2 + 2x - 15 = 0 (x - 3)(x + 5) = 0 x = 3 or x = -5**9. Solve the equation.**e3x + 2 = 40 ln e 3x + 2 = ln 40 (3x + 2) ln e = ln 40 Remember that ln e = 1. 3x + 2 = ln 40 3x = ln 40 - 2**10. Solve for y:**ln y2 +3y - ln (y + 3) = 6 y2 + 3yy + 3 ln = 6 ln(y) = 6 y = e6**SIMPLIFY:**11. ln(e3x) 12. e2ln5x 13. eln7x+9 14. ln( ) 3x (5x)2 = 25x2 _1_e2x eln7x + e97xe9 -2x

More Related